POC14 Treatment-resistant hyponatraemia. Issue 11 (22nd October 2010) - Huda, S; Tyne, H; Marson, A G
Abstract : A 37-year-old female presented with fluctuating focal neurological symptoms, signs and seizures. Initially the aetiology was suspected to be functional but review by the attending neurologist confirmed the diagnosis of cerebral venous sinus thrombosis. Magnetic Resonance imaging showed extensive left cerebral hemisphere infarction. Three weeks after initial presentation she became progressively drowsy coinciding with a decreasing serum sodium level. Examination revealed a dense right hemiparesis (Medical Research Council grading 0/5). She was clinically euvolaemic and blood tests were as follows; serum osmolality 276 mOsmol/kg, urine osmolality 896 mOsmol/kg, urine sodium 141 mmol/l and serum sodium 122 mmol/l. A diagnosis of syndrome of inappropriate antidiuretic hormone (SIADH) was made. Despite fluid restriction and demeclocycline the serum sodium continued to decline to 114 mmol/l. The patient then developed acute renal dysfunction and hypertonic saline was administered. The patient was commenced on the vasopressin antagonist tolvaptan. The serum sodium improved and further pharmacological therapy was not required. The timing, clinical and biochemical picture were convincing for SIADH, however the response to standard initial treatment was more that of cerebral salt wasting syndrome (CSWS). Diagnostic uncertainty between these two conditions remains a challenging situation in both neurology and neurosurgery.